2014
DOI: 10.7812/tpp/13-167
|View full text |Cite
|
Sign up to set email alerts
|

An Audit of Clinician Compliance with Best Practice Recommendations to Repair Severe Obstetric Anal Sphincter Injuries

Abstract: Despite attempts at improving therapeutic outcomes by creating tailored guidelines for repair of obstetric anal sphincter injuries, there is a serious barrier to success because 65% of senior clinicians were noncompliant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…However, educational interventions alone are not enough to make a significant change in practice; compliance with best practice recommendations is an important key for success. Cawich et al [41] found that, despite attempts at improving therapeutic outcomes by creating tailored guidelines for repair of OASI, a serious barrier to success was the finding that 65% of senior clinicians were noncompliant with guidelines [41]. In the current study, we found the use of Table 2 The rate of third-or fourth-degree perineal tears according to medical centre in the pre-and post-workshop periods.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, educational interventions alone are not enough to make a significant change in practice; compliance with best practice recommendations is an important key for success. Cawich et al [41] found that, despite attempts at improving therapeutic outcomes by creating tailored guidelines for repair of OASI, a serious barrier to success was the finding that 65% of senior clinicians were noncompliant with guidelines [41]. In the current study, we found the use of Table 2 The rate of third-or fourth-degree perineal tears according to medical centre in the pre-and post-workshop periods.…”
Section: Discussionmentioning
confidence: 54%
“…Cawich et al . [41] found that, despite attempts at improving therapeutic outcomes by creating tailored guidelines for repair of OASI, a serious barrier to success was the finding that 65% of senior clinicians were noncompliant with guidelines [41]. In the current study, we found the use of the RCOG recommended perineal trauma classification system increased among physicians.…”
Section: Discussionmentioning
confidence: 57%
“…The incidence of 3 rd and 4 th grade perineal tear in United Kingdom was 2.9% (between 0-8%); whereas, 6.1% happened in primiparous and 1.7% in multiparous women. 1,2 Meanwhile, the incidence of 3 rd and 4 th grade of perineal tear in Austria were 1.5% and 0.1%, respectively. 3 The incidence of anal sphincter tear in mediolateral episiotomy population was 1.7% (2.9% on primiparous women) and 12% (19% on primiparous women) in mediana episiotomy population.…”
mentioning
confidence: 99%
“…3 The incidence of anal sphincter tear in mediolateral episiotomy population was 1.7% (2.9% on primiparous women) and 12% (19% on primiparous women) in mediana episiotomy population. 1,2 The 3 rd and 4 th grade perineal tear often induces morbidity for women so that it influences the quality of life. Serious complication on vaginal delivery caused by perineal tear consists of fecal incontinence, pelvic disorders, dyspareuni, chronic pain, and finally it inflicts to social and severe psychological problem.…”
mentioning
confidence: 99%
See 1 more Smart Citation